2016
DOI: 10.1111/ijcp.12856
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of spectral imaging with low-concentration contrast medium in abdominal CT angiography of obese patients

Abstract: Compared with conventional CT, spectral CT imaging significantly reduces both radiation dose and contrast dose while maintaining image quality in abdominal CTA for patients with central obesity and high BMI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 17 publications
0
7
0
1
Order By: Relevance
“…The low-dose MR group had higher CT attenuation than the normal-dose MR group, as lowering tube voltage can significantly increase CT attenuation. When reducing the tube voltage, the IN can be increased, and the SNR or CNR can be reduced (18). However, our study showed that the IN of the low-dose MR group was lower than that of (21).…”
Section: Perioperative Resultsmentioning
confidence: 53%
“…The low-dose MR group had higher CT attenuation than the normal-dose MR group, as lowering tube voltage can significantly increase CT attenuation. When reducing the tube voltage, the IN can be increased, and the SNR or CNR can be reduced (18). However, our study showed that the IN of the low-dose MR group was lower than that of (21).…”
Section: Perioperative Resultsmentioning
confidence: 53%
“…The square of tube voltage is approximately inversely proportional to the radiation dose, and lower tube voltage could reduce the radiation dose more effectively, which has been demonstrated that it could been successfully used in imaging techniques such as CTA. [23][24][25] Some studies showed that kVp may be selected based on body size (body mass index, body width on scout topogram, or patient weight), 26 for example, 100 kVp can be used for patients weighing less than 150 lbs. In our study, the mean weight was 67.68 ± 1.43 (SD) kg (150lbs = 68.0388555 kg).…”
Section: Discussionmentioning
confidence: 99%
“…15 Dual-energy CT is another approach to reduce the amount of contrast medium, while maintaining the image quality. 4,16 As much as 70% reduction in iodine dose with a total amount of 15 g iodine could be achieved using dual-energy CT. 4 One major strength of this technique is that the appropriate monochromatic image could be reconstructed out of multiple energy levels. 16 Another strength is that metal artifacts from stents might be reduced using monochromatic images.…”
Section: Discussionmentioning
confidence: 99%
“…4,16 As much as 70% reduction in iodine dose with a total amount of 15 g iodine could be achieved using dual-energy CT. 4 One major strength of this technique is that the appropriate monochromatic image could be reconstructed out of multiple energy levels. 16 Another strength is that metal artifacts from stents might be reduced using monochromatic images. 17 Combination of dual-energy CT and DRTB method might further reduce the amount of contrast medium necessary for CT of the aorta.…”
Section: Discussionmentioning
confidence: 99%